Seven Notable Legal Developments In Open Source In 2016 (Journal of Open Law, Technology & Society, 2017)
Several noteworthy open source-related legal developments took place in 2016. These concerned the fair use trial in Oracle v. Google, the reaction to the GPL enforcement lawsuits of Patrick McHardy, the dismissal of the Hellwig case, the U.S. Federal Source Code Policy, the end of Eben Moglen's tenure as Free Software Foundation general counsel, the distribution of ZFS by Linux distributions, and the banning of the JSON license by the Apache Software Foundation.